Forms of Legal Protection for Lessors in Leasing Agreements After the Constitutional Court Decision No. 18/PUU-XVII/2019 - Damara Putri, Immaculata; Ketut Rachmi Handayani, I Gusti Ayu; Taruno Muryanto, Yudho; Zefania Ritonga, Rena; Retnowati Boong, Vicariya (Journal of World Science, 2022)
Following on Article 15 Paragraph 2 and Paragraph 3 UU 42/1999, so in practice, Finance Companies, as the lessor, always apply a fiduciary guarantee to the leasing object in the leasing agreement. The power of Fiduciary Deed to execute the leasing object automatically if a debtor breaches of contract has amended its meaning after Constitutional Court released The Decision No. 19/PUU-XVII/2019. It is clearly stated that Finance Companies need a court decision to execute the leasing object of fiduciary guarantee if debtor does not want to surrender the object voluntarily. Therefore, based on utility theory, the purpose of this thesis is knowing whether The Decision No. 19/PUU-XVII/2019 has benefit value for Finance Companies. Then, from this thesis, we want to dig deeper regarding the effort to protect financing companies’ interest in making leasing agreement with debtor. This research is a normative legal research using statute approach, conceptual approach, and case approach. The conclusion of this research is The Decision of Constitutional Court No. 19/PUU-XVII/2019 does not have benefit value for Finance Companies, and also Finance Companies need to more emphasize the leasing agreement related leasing object execution if debtor breaches the contract, then make the leasing agreement become notarial deed.